LEGALIZED EUTHANASIA: A HUMAN RIGHTS AND BIOMEDICAL ETHICAL DIAGNOSIS - van Aardt, Willem (Serbian political thought, 2025)
Euthanasia has been the subject of much legal, religious, moral, and human rights debate in recent years. At the center of this debate is how to reconcile competing values: the wish of patients to choose to die by waiving their right to life through voluntary consent, and the necessity to uphold the inviolable right to life of every person, as recognized by Article 6 (1) of the ICCPR. Even though euthanasia is mostly illegal, there is an ever-increasing drive towards legalization. As more States begin to re-examine and, in some instances, rescind their bans on euthanasia, the international human rights legal community needs to re-examine and reconfirm its viewpoint on the utmost essential human right, that is, the inviolable natural law right to life. By validating euthanasia through national statute, the fundamental human right to live is de facto nullified for many more people than the few whose assumed right to die is compromised. Regrettably, illogical arguments based on obscure and fictional rights, such as “the right to die with dignity,” largely go unopposed, while insistence on respect for true natural law and fundamental human rights, as well as established international jus cogens norms, including the right to life, are negated. The key medical moral criteria— autonomy, beneficence, non-maleficence, and justice — are characterized and illuminated in the context of euthanasia to provide a general, ethical, and moral analytical framework that aids policymakers in making ethically sound judgments.